THE ANALYSIS FOR POSSIBILITIES OF COMMODITY FUTURES INTRODUCTION IN NATIONAL FINANCIAL SYSTEM - Erić, Dejan; Bradić-Martinović, Aleksandra; Stefanović, Saša (Economics of Agriculture, 2007)
The main goal of this Article is to, based on short analysis of basic futures characteristics as commodity and financial instruments, as well as contemporary situation of national commodity and financial market development, study the possibilities for commodity futures introduction in national financial system. The current year proved that unexpected natural circumstances, such as draught, could provoke the weaker harvest in agricultural production, having, on the other hand, many negative consequences, from poor market supply, through higher prices and potential inflation impact, to other market disturbances with many negative effects on general economic stability. The final part of the paper indicates the real possibilities for commodity futures introduction in Serbia, particularly in domain of their application in agribusiness and necessary steps which should be taken in order to realize its development and application.